The founding of Israeli democracy, 1948-1967 - Medding, Peter (New York : Oxford University Press, 1990)
Of the twenty-one countries which established democratic states after 1945, only Israel has remained a functioning democracy, despite the adverse conditions under which it was founded. In this study of Israel's founding years from 1948 to 1967, Peter Medding, a highly regarded scholar of Jewish society and politics, asks why this was the case. He provides a lucid account of the political and historical background to this distinctive period, the political relations which characterized it, and the changes in the balance of forces which brought it to an end. He describes the state-building process and the role played by David Ben-Gurion and other politicians in moving from consensus politics to a majoritarian democracy. Medding's analysis is further enriched by his comparisons of the development of Israeli democracy with that of other countries.
1. The Structures of Democratic Government; 2. Founding an Independent State; 3. Founding Democratic Political Structures; 4. Parties and Policies; 5. Issue Structure, Electoral Response, and Coalition Politics; 6. Coalition Cabinets, Party Government, and the Control of Policy-Making; 7. Mamlakhtiut: Partisan Interests and the Establishment of Centralized and Legitimate State Public Authority; 8. The Political Dynamics of the Founding Period; 9. Conclusion; Appendix A; Appendix B; Select Bibliography; Index
Includes bibliographical references (pages 243-248) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Israel -- Politics and government -- 1948-1967.; Israel -- Politics and government; Israël -- Politique et gouvernement; Israël -- Politique et gouvernement -- 1948-1967.; POLITICAL SCIENCE -- Political Process -- General; Politics and government; Israel; Demokratie; Politisches System; Israel; Israël -- Politique et gouvernement; Israël -- Histoire; Geschichte (1948-1967); 1948-1967; Politics -- History, 1948-1967; Israel; History